2018
DOI: 10.11005/jbm.2018.25.1.23
|View full text |Cite
|
Sign up to set email alerts
|

α-Tocopheryl Succinate Inhibits Osteolytic Bone Metastasis of Breast Cancer by Suppressing Migration of Cancer Cells and Receptor Activator of Nuclear Factor-κB Ligand Expression of Osteoblasts

Abstract: BackgroundBreast cancer is one of the most common cancers affecting women and has a high incidence of bone metastasis, causing osteolytic lesions. The elevated expression of receptor activator of nuclear factor-κB ligand (RANKL) in cancer activates osteoclasts, leading to bone destruction. We previously reported that α-tocopheryl succinate (αTP-suc) inhibited interleukin-1-induced RANKL expression in osteoblasts. Here, we examined the effect of αTP-suc on osteolytic bone metastasis in breast cancer.MethodsTo e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
2
1
0
Order By: Relevance
“…The 4T1 cell migration ability was examined in a 700–1000 µm wound model, as shown in Figure 3E,F and Figure S4 (Supporting Information). In general, free α‐TOS or NP‐TOS15‐treated cells migrated at a much shorter distance (50–100 µm) in 24 h, suggesting that α‐TOS significantly inhibited cancer cell migration 33. Meanwhile, exposure to IFN‐γ (5 ng mL −1 ) decreased the migration distance from 184 to 75 µm (Figure 3E,F), similarly in previous studies 34.…”
Section: Resultssupporting
confidence: 86%
“…The 4T1 cell migration ability was examined in a 700–1000 µm wound model, as shown in Figure 3E,F and Figure S4 (Supporting Information). In general, free α‐TOS or NP‐TOS15‐treated cells migrated at a much shorter distance (50–100 µm) in 24 h, suggesting that α‐TOS significantly inhibited cancer cell migration 33. Meanwhile, exposure to IFN‐γ (5 ng mL −1 ) decreased the migration distance from 184 to 75 µm (Figure 3E,F), similarly in previous studies 34.…”
Section: Resultssupporting
confidence: 86%
“…In addition, EFV reduced the levels of TRAP, DC-STAMP, and cathepsin K expression, which are osteoclast formation and activation-related molecules, by decreasing NFATc1. [3738394041] And we confirmed that RANKL-induced bone resorption was decreased by EFV in vitro. This means that EFV inhibits and reduces the formation and activity of osteoclasts.…”
Section: Discussionsupporting
confidence: 59%
“…NFKB2, one of the plausible upstream genes, encode NF-κB protein that is a transcription factor known as a regulator of the immune system and promotes epithelial-to-mesenchymal transition and the metastasis of BC. [304445] Although the protein encoded by UBIAD1 gene was reported as bladder tumor suppressor protein, there was no report about its role in tumor development or the progression of HEBP1. [46] The UBIAD1 gene had 3 direct cause (parent) genes in S ◆ , i.e., DVL1, INPP1, and MAPK3.…”
Section: Discussionmentioning
confidence: 99%